2015
DOI: 10.7863/ultra.35.5.759
|View full text |Cite
|
Sign up to set email alerts
|

Value of Sonographic Bidirectional Arterial Flow Combined With Elastography for Diagnosis of Breast Imaging Reporting and Data System Category 4 Breast Masses

Abstract: Bidirectional arterial flow evaluation, when combined with elastography, could potentially improve diagnostic accuracy for BI-RADS category 4 breast masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…The presence of BAF was found to have sensitivity of 72.73 per cent and specificity of 64.71 per cent. Our values were slightly different from the results obtained in the study conducted in 116 BI-RADS category 4 lesions by Liu et al 14 who obtained sensitivity of 64.9 per cent, specificity of 98.7 per cent. This disparity could be due to the small sample size used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The presence of BAF was found to have sensitivity of 72.73 per cent and specificity of 64.71 per cent. Our values were slightly different from the results obtained in the study conducted in 116 BI-RADS category 4 lesions by Liu et al 14 who obtained sensitivity of 64.9 per cent, specificity of 98.7 per cent. This disparity could be due to the small sample size used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…at least three positive variables out of eight variables). The diagnostic performance of the combined method was found to have high sensitivity (100%), specificity (76.47%), PPV (89.19%), NPV (100%) and accuracy (92%) in tandem with proposing the combined use of elastography and Doppler to increase the diagnostic performance 13 14 26 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the number of false-positive cases, elastography has been introduced as an additional diagnostic tool to B-mode US which helps clinicians decide whether or not to perform biopsy on USdetected lesions (6)(7)(8)(9)(10)(11)(12)(13). Several studies have evaluated the additional value of elastography in downgrading BI-RADS category 4a lesions detected on US and its effect on reducing the number of unnecessary biopsies being performed (11)(12)(13)(14)(15)(16). In one small series study, none of the BI-RADS category 4a lesions detected on US with soft elastography features was malignant; therefore, they could be managed with follow-up instead of biopsy (11).…”
Section: Introductionmentioning
confidence: 99%
“…In one small series study, none of the BI-RADS category 4a lesions detected on US with soft elastography features was malignant; therefore, they could be managed with follow-up instead of biopsy (11). Other studies also showed that elastography increased specificity when downgrading BI-RADS category 4a lesions and that its addition allowed patients to avoid unnecessary benign biopsies (12)(13)(14)(15)(16). However, biopsy is currently performed for all BI-RADS category 4a breast lesions in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%